AUTHENTIC ASSESSMENT DALAM SISTEM EVALUASI PENGEMBANGAN KURIKULUM 2013 - Muslehuddin Jauhari; Moh. Rofiki; Yudik Al Farisi (Nurul Jadid University, 2017)
Learning assessment is an activity, gathering information and using evidence and feedback from learning outcomes to determine what is learned from the learning process for further learning, and provide the best learning guidance to students so that ultimately the learning objectives can continue. Learning assessment can be done as a reflection and evaluation for the teacher about the learning process that has been done. Assessment of the learning process uses authentic assessment assessment (authentic assessment) that assesses student readiness, process, and overall learning outcomes. The third component will be displayed. Show students the ability, style, and ability to learn or can even produce instructional effects (instructional effects) and the accompanying effects (parenting effects) of learning. The results used are approved by the teacher to be approved for improvement, enrichment (counseling), or counseling services. In addition, the evaluation results can be used as material to improve the learning process in accordance with the Educational Assessment Standards. So based on that, authentic assessment is an assessment carried out to assess the input, process and output of existing learning, there is a feedback system that is managed from documents students learn through exhibitions and examples of work attached to the school environment.